Determination of Magnesium, Zinc, and Reduced Glutathione Levels in Serum of Asthmatic Patients - Naji, N. A (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Asthma is a disease characterized by hyper reactivity of the trachea and bronchi to reversible either spontaneously or as a result of treatment. In this study serum magnesium, Zinc, and reduced glutathione levels were meas ured in order to determine their levels in the asthmatic patients and comparing these levels with healthy controls. Fifty- four asthmatic patients were enrolled in the study and had their pulmonary function test, and the levels of Mg,Zn, and GSH. Serum magnesium and serum zinc were determined by using Atomic Absorption Spectrophotometer . While serum glutathione was determined by spectrophotometric analysis. The asthmatic patients were divided into four groups according to the interpretation of the pulmonary function test : severe expiratory flow limitation, moderate expiratory flow limitation , slight expiratory flow limitation and normal lung values . In this study, it was found that serum magnesium levels in severe cases of asthmatic patients were significantly lower than the healthy control population (0.92 Â± 0.17mmol I L vs.l.O1 Â± 0.19 mmol/L; (p< 0.05 )] while the other cases did not show any significant differences compared with the healthy control . As for serum zinc levels, it was found that the slight cases of asthmatic patients were significantly higher than the healthy control [ 19.48 Â± 1.93 fl mol/L vs. 17.01 Â± 2.94 fl moi/L; (P<0.05 )]. However, the other cases did not show any significant differences compared with healthy control. While serum glutathione levels in severe and slight cases of asthmatic patients were lower than the healthy control. [2.08 Â± 0.51 mmol/L vs. 2.42 Â± 0.21 mmol/L; (P< 0.001), and 1.95 Â±0.36 mmol/ L • 2.42Â± 0.21 mmol/L; (P< O.Ol)],respectively. It was found that there is a correlation between the severity of asthma as measured by pulmonary function test and levels of magnesium and glutathione levels, the more severe one showed low levels of magnesium and glutathione .